Estrategia de marketing en el Comercial "Calzado Lady" de la ciudad de Babahoyo, en el periodo 2023. - Yépez Avilés, Jimmy Manuel (2024)
The objective of the research was to implement a marketing strategy in the "Calzado Lady" commercial in the city of Babahoyo, in the period 2023, and for that it is necessary to use tools such as social networks to direct customers to a website or network. where they can buy the products, so when applying a marketing strategy, sales opportunities are generated, it helps to present and position your company's products and services to reach the target audience through the appropriate channels, in addition to determining the different strategies, the current situation of the marketing strategies in the commercial was diagnosed, which is why it is fundamental in every organization due to the importance it represents, therefore it is advisable that the commercial adopt pertinent measures to apply marketing strategies and protect it efficiently with in order to avoid possible declines in sales. In addition, the qualitative research methodology was used because it was used through the investigation of books, theses, and scientific articles that were incorporated into the conceptual framework. It is also aimed at a type of descriptive research that consists of certain situations. identified in the research process, in addition, information collection techniques or tools were used, such as an interview with the manager of the "Calzado Lady" commercial.